Структурно-анатомічні адаптації листків постійнозелених (напіввічнозелених) видів роду Rhododendron L. (Ericaceae Juss.) - Shumyk, M.I.; Ostapyuk, V.M.; Il'yins'ka, A.P.; Zhuravskiy, R.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The structural and anatomical adaptations of leaves of two evergreen species of the genus Rhododendron L. (R. dauricum L. and R. kaempferi Planch.) studied. Under natural conditions, these rhododendrons are confined to different ecotypes and are distinguished by different frost and winterhardiness. The characteristic features of species and adaptive features of plants determined. Highlighting the most characteristic diagnostic and adaptive structural-foliar features of each species. The studied species have similar anatomical structure of leaves: expressive mesomorphic, dorsoventral mesophyll, poorly developed palisade mesophyll, similar values of the coefficient of palisade, abaxial stomata accommodation, very poorly developed mechanical tissue (collenchyma), as well as a small number of druses of calcium oxalate. Both species are adapted to living in humid environments. R. kaempferi, in comparison with R. dauricum, less suited to functioning in unfavorable conditions. Complex tread indicators leaves R. dauricum features a large number of features and includes a large sheet thickness, two- or threelayer palisad mesophyll, high coefficient of palisade, thickened cell walls of the epidermis. These anatomical features of the leaves, along with the ability to curl up into a tube in the winter, contribute to the existence R. dauricum in the continental climate and the spread in the natural range is wider than it is inherent R. kaempferi.